Membumikan Pelayanan Bagi Kaum Termaginalkan: Kajian Eksegetis-Teologis Atas Mikha 3:1–12 Dalam Konteks Menggereja - Kawangung, Yokibet Henny; Amadeus, Joel Brilian; Saputro, Anon (Hymnos: Jurnal Teologi dan Keagamaan Kristen, 2025)
This article examines Micah 3:1–12 as an exegetical-theological foundation for the church’s efforts to ground its ministry among marginalized communities. Micah 3 exposes the abuse of power by Israel’s leaders who oppressed the poor and violated the principles of God’s justice. Through an exegetical approach, this study interprets Micah’s prophetic message within its historical context and then extracts its theological relevance for the life of the contemporary church. The findings indicate that Micah’s critique of social injustice is not merely a moral exhortation but a prophetic call to redirect the life of God’s people toward His will, which sides with the weak and the oppressed. In the ecclesial context, the text underscores that authentic ministry cannot be separated from the praxis of social justice that upholds human dignity. Thus, Micah 3:1–12 provides a prophetic paradigm that guides the church to be concretely present within social realities and to implement a transformative ministry for marginalized groups.